Caracterización neuropsicológica de adultos mayores con deterioro cognitivo leve. - Besada Mondeja, Nadiara (Universidad Central “Marta Abreu” de Las Villas, 2010)
El presente trabajo se realiza con el propósito de caracterizar las particularidades neuropsicológicas de un grupo de pacientes con deterioro cognitivo leve (DCL) y envejecimiento normal, pertenecientes a casas de abuelos del municipio de Santa Clara, provincia de Villa Clara. La muestra quedó constituida por 43 adultos mayores, de los cuales 23 presentaban un diagnóstico previo de DCL. Se realizó un estudio descriptivo y correlacional, de tipo transversal. Apoyado en la aplicación del Protocolo de Evaluación Neuropsicológica formado por las pruebas: Dígitos del WAIS III; Dibujos del WAIS III; Rompecabezas del WAIS III; Cubos del WAIS III; Lista de palabras WAIS III; FAS; el Stroop, y entrevista estructurada. El estudio se dirigió a la evaluación de la esfera funcional, emocional y cognitiva. Los resultados se analizaron a través de gráficos y tablas en Microsoft Word, Microsoft Excel y las pruebas incluidas en el paquete estadístico SPSS.

The present paper is done with the purpose of characterizing the neuropsychological particularities of a group of patients with mild cognitive impairment (MCI) and normal aging, who belong to elderly nurseries from Santa Clara municipality at Villa Clara province. The sample was composed of 43 elder people, from which 23 presented a previous diagnosis of MCI. A descriptive and correlational study of transversal type was made, based on the application of the Protocol of NeuroPsychological Evaluation composed of the tests: Digits of WAIS III; Draws of WAIS III; Puzzles of WAIS III; Cubes of WAIS III; Word list of WAIS III; Verbal Fluency Test; the Stroop and the structured interview. The study was aimed at evaluating the functional, emotional and cognitive spheres. The results were analyzed through graphs and tables in Microsoft Word, Microsoft Excel and the tests included data pack SPSS. The results showed as main neuropsychological characteristics the deficits in patients with MCI of the functions of attention, visual, verbal, semantic, procedimental and episodic memory, visual constructive, visual perceptive, visual spatial functions. Pre-motors and pre-frontal functions, apart from emotional affections related to depression and affections in the performance of daily instrumental activities. The group of sane elderly people was characterized by a conservation of cognitive functions evaluated, a normal emotional state, where depressed affections are mild and do not show difficulties in the performance of daily instrumental activities. The assessment of the results determined among the variables cognitive functioning according to the level of impairment, age, school level and memory complaint, as well as the correlation of these variables with the performance in the neuropsychological tests. The differences related to the performance of both groups in the tests were also assessed. Conclusions and recommendations are proposed according to the results, especially aimed at the proposal of program of psycho-stimulation for rehabilitation of these patients, the importance of early diagnosis of MCI, the upgrading of the assisting personnel, the family and the promotion of the current line of investigation.
Keywords: Envejecimiento Normal; Deterioro Cognitivo Leve (DCL); Examen Neuropsicológico; Funciones Cognitivas Afectadas; Psicoestimulación Cognitiva; Normal Aging; Mild Cognitive Impairment (MCI); Neuropsychological Test; Affected Cognitive Functions; Cognitive Psycho-Stimulation